Biocompatible Polyelectrolyte Complex Nanoparticles for Lycopene Encapsulation Attenuate Oxidative Stress-Induced Cell Damage - Zhang, Dongjing; Jiang, Yun; Xiang, Ming; Wu, Fen; Sun, Min; Du, XianFeng; Chen, Lei (Frontiers in Nutrition, 2022)
In this study, lycopene was successfully encapsulated in Polyelectrolyte complex nanoparticles (PEC NPs) fabricated with a negatively charged polysaccharides TLH-3 and a positively charged sodium caseinate (SC) via electrostatic interactions. Results showed that the lycopene-loaded PEC NPs were spherical in shape, has a particle size of 241 nm, a zeta potential of -23.6 mV, and an encapsulation efficiency of 93.6%. Thus, lycopene-loaded PEC NPs could serve as effective lycopene carriers which affected the physicochemical characteristics of the encapsulated lycopene and improved its water dispersibility, storage stability, antioxidant capacity and sustained release ability in aqueous environments when compared with the free lycopene. Moreover, encapsulated lycopene could enhance the cells viability, prevent cell apoptosis and protect cells from oxidative damage through Nrf2/HO-1/AKT signaling pathway, via upregulation of antioxidase activities and downregulation of MDA and ROS levels. Therefore, the biocompatible lycopene-loaded PEC NPs have considerable potential use for the encapsulation of hydrophobic nutraceutical in the food and pharmaceutical industries.